Mixed Natural Rubber Latex and Co2SiO4/SiO2 Derived from Silica of Oil Palm Leaves and Cobalt Nitrate - Yudha S, Sal Prima; Adfa, Morina; Istiqphara, Swadexi; Reagen, Muhamad Alvin; Sutanto, Teja Dwi (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Cobalt nitrate solution is combined with oil palm leaf powder to produce a semisolid mixture. The resulting mixture is heated in a furnace at 500 °C for 5 h, producing a grey powder. X-ray diffraction (XRD) analysis of the product showed distinct peaks at 2θ values of 31.2°, 36.8°, 44.8°, 59.2°, and 65.1°, which were consistent with the presence of Co₃O₄/SiO₂. When a similar mixture was heated at 1000 °C for 5 h, a purple powder containing Co₂SiO₄/SiO₂ was obtained. XRD patterns of this material contained peaks at 2θ values of 25.4°, 32.2°, 34.1°, 35.6°, 36.5°, 52.2°, and 62.3°, which corresponded with Co₂SiO₄. The latter product was selected for further analysis, including Fourier-transform infrared (FTIR) spectroscopy which identified characteristic absorption bands at 588 cm⁻¹ and 672 cm⁻¹, alongside additional peaks at 817 cm⁻¹ and 1117 cm⁻¹, reflecting the formation of cobalt silicate. Energy-dispersive X-ray (EDX) analysis confirmed the presence of cobalt (20.7%), silicon (14.0%), and oxygen (45.5%), alongside minor quantities of other elements, while scanning electron microscopy (SEM) showed irregularly shaped, non-spherical particles with some aggregation and a cloudy network. Following characterization, the synthesized cobalt silicate was applied as a colorant in natural rubber latex. Preliminary observations suggest that it functioned effectively as a colorant and remains stable during extended storage. Keywords: Cobalt silicate, cobalt oxide, oil palm leaf (OPL), rubber latex, silica.